2018
DOI: 10.1111/vco.12444
|View full text |Cite
|
Sign up to set email alerts
|

Association of macrophage and lymphocyte infiltration with outcome in canine osteosarcoma

Abstract: Immunotherapeutic strategies have shown promise for the treatment of canine osteosarcoma (cOSA). Very little is known about the immune microenvironment within cOSA, however, limiting our ability to identify potential immune targets and biomarkers of therapeutic response. We therefore prospectively assessed the disease-free interval (DFI) and overall survival time (ST) of 30 dogs with cOSA treated with amputation and six doses of adjuvant carboplatin. We then quantified lymphocytic (CD3+, FOXP3+) and macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 98 publications
(137 reference statements)
1
58
0
Order By: Relevance
“…Broadly, host‐tumour interactions can vary from tumour‐promoting inflammation to effective anti‐tumour immunity . This may begin to explain the somewhat paradoxical increase in CD204+ macrophage infiltration in pulmonary metastases in this study given our previous findings identifying CD204+ macrophages in primary tumours as a positive prognostic factor in cOSA . This shift towards tumour‐promoting inflammation can involve alterations to the functionality of these macrophages between sites of disease .…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Broadly, host‐tumour interactions can vary from tumour‐promoting inflammation to effective anti‐tumour immunity . This may begin to explain the somewhat paradoxical increase in CD204+ macrophage infiltration in pulmonary metastases in this study given our previous findings identifying CD204+ macrophages in primary tumours as a positive prognostic factor in cOSA . This shift towards tumour‐promoting inflammation can involve alterations to the functionality of these macrophages between sites of disease .…”
Section: Discussionmentioning
confidence: 50%
“…For example, Biller et al identified a high CD8+/T‐regulatory cell (Treg) ratio through flow cytometry in the blood as a positive prognostic factor for survival although this did not reach significance within the tumour . In addition, Modiano et al reported that elevated T‐cell infiltrates in cOSA after treatment with Fas‐ligand gene therapy was associated with improved survival, while we identified elevated CD204+ macrophage tumour infiltration as being associated with a prolonged disease‐free interval (DFI) . To the authors' knowledge, the degree of leukocyte infiltration into pulmonary metastatic cOSA is currently unknown however.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations